2009
DOI: 10.1111/j.1464-410x.2009.08688.x
|View full text |Cite
|
Sign up to set email alerts
|

Site of positive surgical margins influences biochemical recurrence after radical prostatectomy

Abstract: to identify preoperative predictors of PSMs and BCR. The estimated 5-year risk of BCR was calculated using the Kaplan-Meier method. RESULTSIn all, 128 (9.8%) men had one or more PSMs. The mean body mass index, mean preoperative serum PSA level, the distributions of clinical stage and biopsy Gleason scores, and the presence or absence of biopsy perineural invasion were significantly different between men with or with no PSMs. In multivariate analysis, baseline serum PSA level, Gleason score and perineural invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 23 publications
3
63
1
2
Order By: Relevance
“…Multifocality of PSMs is predictive of higher BCR rates, but the location of PSMs is less established as a predictor [11] . Godoy et al [7] found in 128 men with PSMs after RP that 5-year actuarial BCR rates varied based on the following rank order of sites of PSMs: base 1 posterolateral 1 apex (100, 49.7, 41.5%, respectively). Tumour volume, lymph node positivity, and the number of positive lymph nodes can also predict BCR [12][13][14] .…”
mentioning
confidence: 99%
“…Multifocality of PSMs is predictive of higher BCR rates, but the location of PSMs is less established as a predictor [11] . Godoy et al [7] found in 128 men with PSMs after RP that 5-year actuarial BCR rates varied based on the following rank order of sites of PSMs: base 1 posterolateral 1 apex (100, 49.7, 41.5%, respectively). Tumour volume, lymph node positivity, and the number of positive lymph nodes can also predict BCR [12][13][14] .…”
mentioning
confidence: 99%
“…By contrast, many studies have shown that quite a lot of men with positive surgical margins never develop biochemical relapse (8)(9)(10).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, several other studies have demonstrated that many men with positive surgical margins do not develop biochemical recurrence (8)(9)(10). As patients with positive surgical margins show an unpredictable clinical course, their proper management still remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in other studies (7,(18)(19)(20). Godoy et al (21) found that even the exact site of positive surgical margins -namely, anterior and basilar -was important and correlated with biochemical recurrence even more than the number of positive margins.…”
Section: Discussionmentioning
confidence: 99%